Immunohistochemical Study of Restorative Composite Monomers Effect on Dental Pulp Vitality Using Biomarkers Ki-67 and p53 (Journal of Hama University, 2020)
The sides effects of dental caries preparation and restoration on pulp vitality vary significantly, and could exacerbate in deep restorations, leading to serious functional disorder then necrosis of pulp at the long term. The aim of this study is to investigate the effect of monomers penetration of deep composite restoration, via dentinal tubuli, on the rate & nature of cellular division in dental pulp. Human teeth, scheduled for orthodontic extraction, have been used, where divided into (9) groups to follow the effects of etching technique, and light-curing period of deep composite restorations on cellular division in dental pulp, using immunohistochemical marking via monoclonal antibodies Ki-67 and p53. Marking carried out after 3 weeks and 3 months from restoration, modifications in Ki-67 and p53 expression levels were followed, and function of gradual quantitative criteria regarding spreading and concentration index of pulpal stained cells. Statistical Analysis (P